Kepatuhan Syariah dalam Transformasi Digital pada layanan mobile Banking Syariah - SYAKARNA, NUGRAHENI_; Syakarna, Nugraheni Fitroh Rezqi; Islahudin, Ahmad Noor (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2026)
This study aims to examine how Islamic banks in Indonesia implement digital transformation in mobile banking services while maintaining Shariah compliance, identify factors influencing the effectiveness of digital Shariah governance, and explore customers’ perceptions and experiences of these services. This research employs a qualitative method using a case study and Interpretative Phenomenological Analysis (IPA) approach. Data were collected through in-depth interviews, non-participatory observations, and document analysis, and were analyzed using the Miles, Huberman, and Saldaña framework. The findings reveal that Islamic banks have adopted technologies such as AI, blockchain, smart contracts, and automated Shariah notification features. However, digitalization still faces challenges, including limited technological competence among Sharia Supervisory Board members, insufficient development of digital Shariah governance frameworks, and the lack of maqāṣid al-sharī‘ah integration into digital product design. Customer perceptions indicate generally positive experiences regarding convenience and security, although understanding of Shariah principles within mobile applications remains limited. This study highlights the importance of value-based digital transformation that prioritizes not only technological efficiency but also strengthens Shariah compliance and customer trust.